Digital Identity - Majeed Mohamed Fareed Majeed; Abdurahman Adisaputera; Muhammad Ridwan (Budapest International Research and Critics University, 2020)
With the penetration and spread of the Internet in our daily life, issues related to our identity on the Internet and their potential impacts on our lives, whether positive or negative, have become very important. We, as individuals, interact with a number of websites and services on the Internet that require an account (username and password) to access. These sites range from simple news sites that limit the number of articles that you can read anonymously in a certain period of time, to financial services or healthcare sites or others. Similar services on the Internet require that you know with certainty that you are definitely